Turismo, desenvolvimento e pobreza em Moçambique: analisando o caso do Município de Inhambane - Benjamim, Leonildo Fernando (2024)
In the research, we analyze the contribution of tourism to promoting development and reducing poverty in IM (Inhambane Municipality). The research is part of the problematic economic perspective that claims that tourism is a universal panacea, with the capacity to solve all social and economic challenges, ensuring progress through the creation of jobs and income, multiplier effects, stimulating entrepreneurship, among other aspects. To this end, we characterized the dynamics of tourism in order to gauge the current level of general tourism supply in the IM; we investigated the existence and applicability of public tourism policies to promote development in the IM; we researched the participation of local communities in tourism businesses and in the decision-making system in general, so that they can make the most important choices that can improve their lives. In the methodological approach, we used bibliographical and documentary research, defined the research variables, carried out non-participant observation and exploratory interviews, basically to problematize and define a theoretical framework to guide the research. We used mixed surveys, interviews and observation to collect data. We adopted purposive sampling for the government and accessibility sampling for direct contact with local communities in the parishes of Barra, Tofo, Tofinho and Inhambane City. We also used systematic observation scripts for the variables related to tourism-based social development in IM. Finally, we analyzed and interpreted the results using the technique known as content analysis, based on reflective and critical interpretation; in addition, we presented the results through tabulation, images and interview excerpts. Our analysis indicates that tourism has made a contribution (albeit limited) to advancing development. However, issues persist such as centralization and politicization in decision-making, restrictions on freedom, job insecurity, disrespect for workers’ rights, informality in local economies without negotiating power, neglect of the social responsibilities of companies and local government, seasonal unemployment, low levels of education, social inequalities, silencing of local voices, corruption, weak public-private partnerships, among other limits and difficulties. These challenges contrast with the vision of development defended in the research, which emphasizes increasing capacities beyond the financial aspect, so that communities are the agents or subjects or protagonists of development and not merely a vulnerable object in need of assistance. Consequently, it seeks to achieve higher levels of autonomy, quality of life, well-being, happiness and freedom. As a contribution, the research has the potential not only to add value to the sphere of resistance and alternative reflection on development, but it can also be an effective tool for sensitizing authorities to the importance of strengthening local communities through tourism.